O'Reilly software architecture conference 2019, New York, New York. (O'Reilly Media, 2019)
"What do you really need to consider when adopting a microservices architecture? How do you unite large groups of talented and highly opinionated engineers around a single CI/CD framework? Kubernetes is catching on like wildfire, but how do you ensure that your legacy application can take advantage of everything Kubernetes has to offer? These are just three of the many real life issues addressed in this video compilation of the talks delivered this year by some of software architecture's best and brightest at SACON New York 2019. Designed for engineers, developers, tech leads, and managers, this video compilation of SACON New York 2019 contains the information you need to stay ahead of the curve in the ever evolving world of software architecture."--Resource description page